The Political Economy of Regional Power: Turkey under the AKP - André Bank; Roy Karadag (German Institute of Global and Area Studies (GIGA), 2012)
In 2006/2007 Turkey became a regional power in the Middle East, a status it has continued to maintain in the context of the Arab Spring. To understand why Turkey only became a regional power under the Muslim AKP government and why this happened at the specific point in time that it did, the paper highlights the self-reinforcing dynamics between Turkey's domestic political-economic transformation in the first decade of this century and the advantageous regional developments in the Middle East at the same time. It concludes that this specific linkage - the Ankara Moment - and its regional resonance in the neighboring Middle East carries more transformative potential than the Washington Consensus or the Beijing Consensus so prominently discussed in current Global South politics.
Keywords: 300; regional power; political economy; Turkey; AKP; Middle East; Großmacht; Mittlerer Osten; Ideologie; Politischer Wandel; Türkei